Supervisory oversight role for the central bank to raise awareness of the banking supervisory: Applied Research in the Central Bank of Iraq and a sample of the Iraqi private banks (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Representing banking supervision An important function performed by the Iraqi Central Bank, in order to achieve stability in the financial and banking system, and safeguard the rights of depositors, investors and other targets, and to realize the Iraqi Central Bank banking supervision actors on banks, there must be an awareness of regulatory bank's existing control and subject them, as well as the role of banking oversight interested in spreading this awareness. So sought search to find out the role played by the Iraqi Central Bank in raising awareness of the regulatory banking between the parties to the regulatory process, through the presentation and analysis of the legal framework for banking supervision and awareness supervisory banking, as well as analysis of the views of a sample of the various communities, which represent the parties the regulatory process, and by measuring banking supervisory awareness of these parties. Search it built on the basic premise (that the banking supervisory awareness by the Central Bank of Iraq's existing oversight and subject them and interested in them) leads to: - 1- improve performance for those in charge of banking supervision and subject to them.2- To maintain public money and private equity.3- Quality audit work for those in charge of banking supervision.This has been proven this hypothesis and to reach a set of conclusions, including: the importance of the role played by the Central Bank of Iraq in the banking supervisory awareness among the parties to the regulatory process, As well as the lack of a modern guide regulating the actions of banking supervision of the staff of the Central Bank of Iraq.As output Find a set of recommendations including: focus by the Iraqi Central Bank on the rehabilitation and development of the skills of banking supervision of his employees, and attention to the human element in order to keep pace with the global development through training courses in the field of banking supervision, so as to increase awareness of the regulatory banking have, and that reflected on the exercise of effective banking supervision on banks